Increasing use of newer antiseizure medication during pregnancy: An observational study with special focus on lacosamide. (April 2023) - Hoeltzenbein, Maria; Slimi, Sofia; Fietz, Anne-Katrin; Stegherr, Regina; Onken, Marlies; Beyersmann, Jan; Dathe, Katarina; Schaefer, Christof
Highlights: Pregnant women are increasingly exposed to newer antiseizure medication like lacosamide although their safety has not been evidenced yet. Preliminary data indicate no increased risk for spontaneous abortion or major birth defects related to lacosamide during pregnancy. Effects of newer antiseizure medication on pregnancy outcome are difficult to specify, because of limited numbers of well documented pregnancies, frequent antiseizure co-medication and a high rate of terminated pregnancies. Abstract: Introduction: Epilepsy is a common neurological disease requiring long-term therapy also during pregnancy. Most studies on pregnancy outcomes in women with epilepsy are based on antiseizure medication (ASM) in monotherapy. However, about 20–30% of epilepsy patients require polytherapy and newer ASMs are an option, when seizure control is not achieved with first line ASMs. Methods: Observational study evaluating the use of newer ASMs with marketing authorization since 2005 reported to the Embryotox Center of Clinical Teratology and Drug Safety in Pregnancy between 2004 and 2019. In addition, course and outcome of lacosamide exposed pregnancies were analysed. Results: Our study confirms the increasing use of newer ASMs also in pregnant women. This is especially true for lacosamide, eslicarbazepine and brivaracetam with rising numbers of exposed pregnancies soon after marketing authorization. Analysis of 55 prospectively and 10 retrospectively ascertained lacosamide exposed pregnancies does not indicate increased risks of major birth defects or spontaneous abortion. However, bradycardia observed in 3 neonates might be related to prenatal lacosamide exposure. Conclusion: Available data do not support the assumption of lacosamide being a major teratogen. The increasing use of newer ASMs during pregnancy underscores the need for more studies to guide preconception counselling, especially for lacosamide, eslicarbazepine and brivaracetam.